In Vitro Tissue Regeneration by Human Degenerated Nucleus Pulposus Cells in Hyperosmotic Culture Medium. (May 2014) - Krouwels, A.; Popov, J.; Plomp, S.; Dhert, W.; Oner, C.; Bank, R.; Creemers, L.
Introduction: Healthy intervertebral disc (IVD) cells normally reside in a high osmolality environment of 450 to 550 mOsm/kg and extracellular matrix production by MSC cells has been shown to increase with increasing osmolality. However, it is not known how human degenerated disc cells are affected by osmolality. The aim of the current study was to determine the effects of osmolality on tissue regeneration by human degenerated NP cells. Materials and Methods: The osmolality of standard chondrogenic culture medium (DMEM, 2% ascorbic acid-2 phosphate, 2% human serum albumin, 2% insulin-transferring selenium-X, 1% penicillin/streptomycin, 10 ng/mL transforming growth factor β2 [TGF-β2]) was adjusted with NaCl and sucrose from 340 to 400, 450, and 500 mOsm/kg. IVD cells from four human donors (Thompson grade III) were cultured for 28 days in high density (1*10^6 cells/cm 2 ) on collagen II coated filters. LDH analysis was performed to analyze toxicity. Samples were stained with Safranin-O for glycosaminoglycans (GAGs) and with immunohistochemistry for collagen II. Gene expression was evaluated by qPCR and a collagen low-density array. Matrix content as reflected by glycosaminoglycan (GAG) production was measured with a dimethylmethylene blue (DMMB) assay and DNA content with a Picogreen assay. Statistical analysis included univariate analysis of variance with randomized block design and post hoc Dunnet t -test. Results: No cytotoxic effects were found in any of the conditions tested. Gene expression showed an osmolality-dependent increase compared with standard medium in collagen II and aggrecan only when NaCl was used (see Fig. 1A, B for p -values). However, at the protein level, no effect of increased osmolality using NaCl was found. This could not be explained by MMP gene expression levels, as these seemed lower at high osmolality. Tissues cultured in the presence of the osmolyte sucrose appeared to contain less proteoglycans, but this difference was not significant. Conclusion: In conclusion, in the current culture system, the increased expression of matrix genes with osmolality appears to be osmolyte dependent rather than osmolality dependent. Moreover, the absence of an effect at the protein level suggests adjusting osmolality with NaCl to enhance matrix production by IVD cells is not required. Disclosure of Interest None declared